PIPE STUCK CAUSES ANALYSIS AND PREVENTIVE ACTIONS IN GEOTHERMAL DRILLING WELL AWI FIELD GUNUNG SALAK BASED ON PREVIOUS DRILLING PROBLEMS - Hezron Byrian Manurung (Journal of Petroleum and Geothermal Technology, 2022)
The stuck pipe incident occured four times in three wells located on pad AWI-9. The three wells that experienced the stuck pipe were occurred first at AWI well 9-3, then twice at AWI well 9-5 and finally at AWI well 9-7. The first stuck pipe incident occurred at AWI 9-3 at the depth of 4,248 ftMD or 1,294 meters. There is a change in elemental anomalies or mud properties, an increase in the chloride property from the presence of brine in the wellbore as well as the increase of torques as a result of the accumulation of cuttings around the drill pipe assembly which resulted in sloughing or formation collapse. The next stuck pipe incident came from the AWI 9-5 well which occurred at the depth of 3,478 ftMD or 1,060 meters and at 4,667 ftMD or 1,422 meters. The background of the stuck pipe in this well can be seen from the collapse of the Paleosoil formation, the decrease in pump rate due to damage of the mud pump and the absence of air use when drilling in a loss circulation circumstances. This latter hindrance also led to the stuck pipe incident in the AWI 9-7 well at a depth of 6,266 ftMD or 1,910 meters. The overall occurrence of stuck pipes in the three wells above can be overcome and the drill pipe series can be released through working pipe efforts, maximizing the use of air and conducting well heat-ups. The methodology used in this thesis is a study of sub-surface and surface data during and before the occurrence of the stuck pipe incident. The data are log data in the form of daily drilling report, drill cutting or cutting data, drilling parameters and periodic reports of drilling mud per well. From the analysis of the data above, it was found that preventive measures were taken to prevent the same thing from re-occuring. The form of adding a mud additives that function as a reduction or prevention of fluid loss so that the loss circulation conditions can be prevented and brine and formations that have sloughing properties as the cause of collapse will not enter the hole, maintaining the weight of the mud and viscosity so that the mud cake maintained and the hole wall remains strong and the importance of hole cleaning during the drilling process; this includes the time before the connection process or removing the pipe circuit and the importance of using air in geothermal drilling which has a loss circulation character.